Traffic Engineering and Transport Planning - L. R. Kadiyali (Delhi, Khanna Publishers, 2018)
This subject is growing and its important as the vehicle population increases, and the attendant problems become alarming. Considering the relevance of the subject to our times is being offered to the undergraduate and post-graduate students in the discipline of Highway Engineering and Traffic Engineering, Professional Highway Engineers and Traffic Transportation Engineers and Town Planners in India. In fact, Traffic engineering has a multi-disciplinary coverage, and includes engineers, planners, statisticians, the police, administrators and so on. The book through its 51 Chapters covers following topics.
Keywords: Traffic Engineering I Transport Planning I Civil Engineering